Dreamnesting – Co-created future vision of an intelligent interior design experience - Kymäläinen, Tiina (Futures : the journal of policy, planning and futures studies, 2013)
•Science-fiction prototype about interior design in an intelligent environment.•Novel service concepts for making interior and renovation designs.•Platform for implementing the ideas for new interactions.•Customer experience at the centre of the platform. This article, and subsequent science-fiction prototype, finds its premise in two different foundations: the human-centred design of new technology development, and the co-creation methodologies of business sciences. The connection between these two research fields arises from the emerging need to find means of constructing complex service experiences with multidisciplinary approach. By leaning on both perspectives, the aim of the article is to construct a science-fiction prototype ‘Dreamnesting’. The prototype presents a new service enterprise that engages a user–customer deeply in the co-creation experience and introduces a new technology platform for the interior design task: augmented reality (AR) technology in an intelligent service environment. The prototype has its foundations, at first, in a front-end co-design user study, which aimed at creating novel interior design service concepts that were thought to be used virtually, and to exploit 3D modelling and AR technology. Then, the article converses on relevant building blocks that come to the fore from the economy and business theories, namely: co-creation of value, customer experience and human assets of the firm.